An Investigation Into Stakeholders' Perceptions of the Youth-to-Senior Transition in Professional Soccer in the United Kingdom. Issue 4 (1st October 2016) - Morris, Robert; Tod, David; Oliver, Emily
Abstract : The youth-to-senior transition in professional soccer within the UK is challenging, yet previous work has focused on perspectives of a limited range of within-sport stakeholders. We conducted semistructured interviews with coaches ( n = 12), sport science support staff ( n = 10), and parents of players ( n = 6), exploring their perceptions of transition demands, resources, and barriers. Emergent themes highlighted role-specific support provision and that athletes progress through a period of adaptation, requiring a diverse set of characteristics and resources (e.g., knowledge of the transition process, social support), developed through a number of preceding transitions.